Two aquaporins, PIP1;1 and PIP2;1, mediate the uptake of neonicotinoid pesticides in plants - Qun Wan; Yixin Li; Jinjin Cheng; Ya Wang; Jing Ge; Tingli Liu; Liya Ma; Yong Li; Jianan Liu; Chunli Zhou; Haocong Li; Xing Sun; et al. (Plant Communications, 2024)
Neonicotinoids (NEOs), a large class of organic compounds, are a type of commonly used pesticide for crop protection. Their uptake and accumulation in plants are prerequisites for their intra- and intercellular movements, transformation, and function. Understanding the molecular mechanisms that underpin NEO uptake by plants is crucial for effective application, which remains elusive. Here, we demonstrate that NEOs enter plant cells primarily through the transmembrane symplastic pathway and accumulate mainly in the cytosol. Two plasma membrane intrinsic proteins discovered in Brassica rapa, BraPIP1;1 and BraPIP2;1, were found to encode aquaporins (AQPs) that are highly permeable to NEOs in different plant species and facilitate NEO subcellular diffusion and accumulation. Their conserved transport function was further demonstrated in Xenopus laevis oocyte and yeast assays. BraPIP1;1 and BraPIP2;1 gene knockouts and interaction assays suggested that their proteins can form functional heterotetramers. Assessment of the potential of mean force indicated a negative correlation between NEO uptake and the energy barrier of BraPIP1;1 channels. This study shows that AQPs transport organic compounds with greater osmolarity than previously thought, providing new insight into the molecular mechanisms of organic compound uptake and facilitating innovations in systemic pesticides.